PERBEDAAN HASIL BELAJAR PESERTA DIDIK ANTARA MODEL PEMBELAJARAN CERAMAH DAN MODEL PEMBELAJARAN NUMBERED HEADS TOGETHER PADA MATA PELAJARAN SOSIOLOGI - Komsiana, Komsiana (Solidarity: Journal of Education, Society and Culture, 2012)
To get quality human resource, we need a model of learning and teaching strategy that can improve the educational system . This model should not only require students to memorize facts, but also encourage students to mind and construct their own knowledge. One model of learning that can be used to improve learning is the learning outcomes numbered heads together (NHT). The purpose of this study was to determine the differences in learning outcomes by using a model of learning and NHT lectures on subjects in high school sociology class X Semarang State 14. The results showed that using the model of lecture learning students feel bored and sleepy with the average results of the cognitive aspects of learning, reaching 70.64. On learning NHT model, students are able to unite a lot of thought and intelligent students who can interact well with students who are less proficient with the average yield reached 76.19 evaluation tests. From these results we can conclude that learning by using learning models NHT is better than using a model of lecture-based learning.